In vitro culture and diversity of endophytic fungi in Bambusa oldhamii - Ana Paula de Azevedo Pasqualini; Mariely Cristine dos Santos; Bruno Francisco Sant´Anna-Santos; Hugo Pacheco de Freitas Fraga; Marguerite Quoirin (Pesquisa Agropecuária Tropical, 2019)
Bambusa oldhamii Munro is a fast-growing species of woody bamboo with strong commercial appeal. In Brazil, the use of this species is limited, mainly due to the low availability of seedlings for commercial plantations. Micropropagation is a technique used for the large scale production of seedlings, but protocols for the establishment of aseptic cultures are hampered by the presence of endophytic contamination. This study aimed to develop an in vitro establishment protocol for B. oldhamii, as well as to make the molecular identification of fungi associated with the explants used. Nodal segments of adult plants grown in the field were used as explants. This material was submitted to two experiments carried out to evaluate the effect of 6-benzylaminopurine (BAP) on multiplication and of Plant Preservative Mixture (PPMTM) as a disinfectant. In the first one, 10 µM, 15 µM or 20 µM of BAP were combined with 1 mL L-1, 2 mL L-1 or 3 mL L-1 of PPMTM; while the second one used 0 µM, 2.5 µM, 5 µM or 7.5 µM of BAP with 4 mL L-1 of PPMTM, both added to MS culture medium. After 21 days of culture, the use of 4 mL L-1 of PPMTM inhibited the bacterial growth and reduced fungal contamination. The addition of BAP to the culture medium above 10 µM inhibited the formation and growth of new shoots, while additions of less than 7,5 µM had no effect. The molecular identification of the endophytic fungi isolated during the in vitro culture indicated the presence of numerous fungal species, increasing the current knowledge about the diversity of fungi associated with bamboo.